The development and implementation of an android-based saving and loan cooperative application - Moechammad Sarosa; Devi Khanthi Dwi Bhakti; Putri Elfa Mas'udia; Yunia Mulyani Azis; Nailul Muna; Ekananda Sulistyo Putra (Institute of Advanced Engineering and Science, 2021)
The savings and loans cooperative are a cooperative that has an important purpose in its reach and services, such as the Permata Ngijo Savings and Loans Cooperative. Activities within the cooperative itself include managing member data as well as savings and loan transactions. In systems that are still manual, such as Microsoft Excel, there is a risk of inaccurate data and takes a long time. This manual system is still less effective because the number of members and transactions continues to grow. Therefore, an application is needed as a more effective data processing and information system for members that is easier to access. This study aims to build an android-based savings and loan application using the hypertext preprocessor (PHP) programming language and my structured query language (MySQL) as data storage. Based on the android application that has been made, it shows that the black box functionality of the application runs as planned, the success rate for users reaches 90%.